Diagnostic performance of the endoscopic pressure study integrated system (EPSIS): a novel diagnostic tool for gastroesophageal reflux disease - Inoue, Haruhiro; Shimamura, Yuto; Rodriguez de Santiago, Enrique; Kobayashi, Yasutoshi; Ominami, Masaki; Fujiyoshi, Yusuke; Sumi, Kazuya; Ikeda, Haruo; Onimaru, Manabu; Manolakis, Anastassios C. (Endoscopy, 2019)
Background The endoscopic pressure study integrated system (EPSIS) is a prototypic system for monitoring intragastric pressure (IGP) fluctuations that result from opening of the cardia during gastric distension. The performance of EPSIS for the diagnosis of gastroesophageal reflux disease (GERD) was evaluated.Methods A retrospective analysis was conducted of data prospectively collected over a 2-year period from 59 patients who underwent gastroscopy, EPSIS, and 24-hour pH monitoring. Using a dedicated electronic device and a through-the-scope catheter, maximum IGP (IGPmax) and IGP waveform pattern (uphill/flat) were recorded.Results The optimal IGPmax cutoff was 18.7 mmHg. IGPmax < 18.7 mmHg (sensitivity 74.2 %, 95 % confidence interval [CI] 56.8 – 86.3; specificity 57.1 %, 95 %CI 39.1 – 73.5) and flat pattern (sensitivity 71.0 %, 95 %CI 53.4 – 83.9; specificity 82.1 %, 95 %CI 64.4 – 92.1) were associated with GERD. “Double” EPSIS positivity (IGPmax < 18.7 mmHg and flat pattern) provided maximum specificity (85.7 %, 95 %CI 68.5 – 94.3), whereas “any” EPSIS positivity (IGPmax < 18.7 mmHg or flat pattern) provided maximum sensitivity (80.6 %, 95 %CI 63.7 – 90.8). Maximum specificity and sensitivity for nonerosive reflux disease (NERD) was > 70 %. In multivariate analysis, “double” EPSIS positivity was the strongest predictor of GERD (odds ratio [OR] 16.05, 95 %CI 3.23 – 79.7) and NERD (OR 14.7, 95 %CI 2.37 – 90.8).Conclusion EPSIS emerges as a reliable adjunct to routine gastroscopy for GERD diagnosis, and might prove helpful for the stratification and management of patients with reflux disorders.